2012
DOI: 10.1371/journal.pone.0042976
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Metastasis Suppressor 1 Regulates Hepatocellular Carcinoma Cell Apoptosis via Suppressing Osteopontin Expression

Abstract: Breast cancer metastasis suppressor 1 (BRMS1) was originally identified as an active metastasis suppressor in human breast cancer. Loss of BRMS1 expression correlates with tumor progression, and BRMS1 suppresses several steps required for tumor metastasis. However, the role of BRMS1 in hepatocellular carcinoma (HCC) remains elusive. In this study, we found that the expression level of BRMS1 was significantly down-regulated in HCC tissues. Expression of BRMS1 in SK-Hep1 cells did not affect cell growth under no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 61 publications
1
20
0
1
Order By: Relevance
“…Low expression of the metastasis suppressor BRMS1 was recently shown to be an independent prognostic factor for poor prognosis both for metastasis-free survival and overall survival in nasopharyngeal carcinoma patients [34]. In a recent study, Wu et al found that the expression level of BRMS1 was significantly down-regulated in hepatocellular carcinoma (HCC) tissues and that BRMS1 sensitizes HCC cells to apoptosis [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Low expression of the metastasis suppressor BRMS1 was recently shown to be an independent prognostic factor for poor prognosis both for metastasis-free survival and overall survival in nasopharyngeal carcinoma patients [34]. In a recent study, Wu et al found that the expression level of BRMS1 was significantly down-regulated in hepatocellular carcinoma (HCC) tissues and that BRMS1 sensitizes HCC cells to apoptosis [35]. …”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that PAEP promotes tumor cell growth at least in part by downregulating TSP-1 expression. The presence of SPP-1, a putative tumor oncogene (30)(31)(32), in the medium was lost following the knockdown of PAEP. Thus, secretion of SPP-1 is directly related to the presence of PAEP.…”
Section: Discussionmentioning
confidence: 99%
“…The human miR-125a-5p plasmids, miR-control plasmids, anti-miR-125a-5p and anti-miR-control were designed and generated by Shanghai GenePharma Co., Ltd., Shanghai, China (Shanghai, China). The siR NA small-inter fering (si)R NA (#S1 sequence, 5'-GGAAUAAGUACGGAAUGUGA-3') that targets the BRMS1 gene was synthesized by Guangzhou RiboBio Co., Ltd., (Guangzhou, China) as previously described (25). Additionally, the coding sequences [without the 5'-untranslated region (UTR) of BRMS1] was amplified by PCR and cloned into the pcDNA3.1 (+) vector (Shanghai GenePharma Co., Ltd).…”
Section: Rna Extraction and Reverse Transcription-quantitative Polymementioning
confidence: 99%